TyG Index Change Is More Determinant for Forecasting Type 2 Diabetes Onset Than Weight Gain. Issue 19 (May 2016) - Navarro-González, David; Sánchez-Íñigo, Laura; Fernández-Montero, Alejandro; Pastrana-Delgado, Juan; Martinez, Jose Alfredo
Abstract : Abstract: The risk of type 2 diabetes associated with obesity appears to be influenced by other metabolic abnormalities, and there is controversy about the harmless condition of the metabolically healthy obese (MHO) state. The aim of this study is to assess the risk of diabetes and the impact of changes in weight and in triglyceride-glucose index (TyG index), according to the metabolic health and obesity states. We analyzed prospective data of the Vascular Metabolic CUN cohort, a population-based study among a White European population (mean follow-up, 8.9 years). Incident diabetes was assessed in 1923 women and 3016 men with a mean age at baseline of 55.33 ± 13.68 and 53.78 ± 12.98 years old. A Cox proportional-hazard analysis was conducted to estimate the hazard ratio (HR) of diabetes on metabolically healthy nonobese (MHNO), metabolically healthy obese, metabolically unhealthy nonobese (MUNO), and metabolically unhealthy obese (MUO). A continuous standardized variable ( z -score) was derived to compute the HR for diabetes per 1-SD increment in the body mass index (BMI) and the TyG index. MHO, MUNO, and MUO status were associated with the development of diabetes, HR of 2.26 (95% CI: 1.25–4.07), 3.04 (95% CI: 1.69–5.47), and 4.04 (95% CI: 2.14–7.63), respectively. MUNO individuals had 1.82 greater risk of diabetes compared to MHO subjects (95% CI: 1.04–3.22). The HRs for incident diabetes per 1-SD increment in BMI and TyG indexes were 1.23 (95% CI: 1.04–1.44) and 1.54 (95% CI: 1.40–1.68). The increase in BMI did not raise the risk of developing diabetes among metabolically unhealthy subjects, whereas increasing the TyG index significantly affect the risk in all metabolic health categories. Metabolic health is more important determinant for diabetes onset than weight gain. The increase in weight does not raise the risk of developing diabetes among metabolically unhealthy subjects.